2013
DOI: 10.1590/s0034-89102013000100013
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de medicamentos por idosos, Goiânia, Brasil

Abstract: OBJECTIVE:To analyze the pattern of use of medications use in aged people and associate it with socioeconomic aspects and with the self-rated health. METHODS:A population-based cross-sectional design study with 934 elderly people from Goiania, Midwestern Brazil, between December 2009 and April 2010. Data were collected through a questionnaire. The dependent variable was the number of medications consumed and the independent variables were sex, marital status, education, type of residence, age, income, and self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
39
1
93

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(142 citation statements)
references
References 18 publications
9
39
1
93
Order By: Relevance
“…These results corroborate the morbidity profile found and the results obtained in the study carried out in Goiânia (Goias) 16 . They are also linear to the prevalence and accumulation of pathologies of these systems which, in this age group, often require pharmacological interventions for their control.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results corroborate the morbidity profile found and the results obtained in the study carried out in Goiânia (Goias) 16 . They are also linear to the prevalence and accumulation of pathologies of these systems which, in this age group, often require pharmacological interventions for their control.…”
Section: Discussionsupporting
confidence: 91%
“…In terms of reported medical diagnosis, diseases of the Cardiovascular System (Hypertension), the Endocrine System (Type 2 Diabetes Mellitus and Hypothyroidism) and Infectious (Cold/Flu) and Osteoarticular diseases (chronic joint pain) were the most prevalent, data that reinforces the findings of other studies 16,17 . These conditions require constant monitoring by health teams and proper monitoring and control, as well as the regular dispensing of medications.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…10 Brazilian studies report that self-medication with analgesics is a common occurrence among the elderly, as the use of such medication is related to the treatment of pain and inflammation, common symptoms for this age group. [11][12][13] The American Geriatrics Society Panel on Persistent Pain among the Elderly 14 found that non-opioid analgesics are the most widely used drugs for pain management, although studies 12,14,15 have found an increase in the use of opioid analgesics in Europe and North America. Opioid analgesics provide an analgesia for moderate to severe pain, but should be used with caution as they can cause constipation, respiratory depression and dellirium.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, elderly persons are more likely to use a number of drugs as they undergo more physiological changes in pharmacokinetics and pharmacodynamics due to their age 6 . The frequent simultaneous use of many drugs by the elderly has also been identified.…”
Section: Introductionmentioning
confidence: 99%